PENGARUH MODAL DAN LAMA USAHA TERHADAP PENDAPATAN PEDAGANG DI PASAR TRADISIONAL PASAR MINGGU - Rani rani (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Indonesia has a relatively high growth rate, large population, poverty, a young age structure, and uneven population distribution. a large population is a basic capital in achieving national development goals if improper management will cause problems in the field of employment. High levels of unemployment have an impact on the informal sector which can overcome these problems. Informal sector activities usually occur in very densely populated areas that are concentrated in urban areas. Less formal education, untrained and lack of access to capital, resulting in low income in the formal sector. This study aims to determine the factors that influence the seller's income that have a dominant influence on income. This study uses primary data taken from 50 respondents with the census method and analyzed using multiple linear regression. The results show that business experience and capital greatly affect the seller's income. This study also shows that business experience is the most influential factor in the sellers' income compared to other factors. To increase the income of traditional sellers, the right business strategy is needed by providing training, coaching, and counseling so that traditional sellers can provide excellent service to buyers.